2011
DOI: 10.4161/cib.15552
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating axon regeneration in the injured CNS by microtubules stabilization

Abstract: Traumatic CNS injuries often cause permanent, devastating disabilities due to a lack of regeneration of damaged axons. Next to an insufficient intrinsic capability of CNS neurons to regrow axons, also inhibitory molecules that are associated with the CNS myelin and the glial scar contribute to the failure of axonal regeneration. Strategies targeting the inhibitory molecules, their receptors or downstream signaling pathways result in little improvement of regeneration in vivo. However, the combination of such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…Treatment for spinal cord injury depends on axon regeneration and appropriate synapse formation. Several reports implicate microtubule stabilization in facilitating axon regeneration (85,86). Our results showed that Atat1 is the sole ␣-tubulin acetyltransferase in the brain (Fig.…”
Section: Atat1supporting
confidence: 57%
“…Treatment for spinal cord injury depends on axon regeneration and appropriate synapse formation. Several reports implicate microtubule stabilization in facilitating axon regeneration (85,86). Our results showed that Atat1 is the sole ␣-tubulin acetyltransferase in the brain (Fig.…”
Section: Atat1supporting
confidence: 57%
“…Although AAV-hIL-6 was applied right after optic nerve lesion instead of prior to injury as described for previous experimental manipulations, the regenerative response was even comparable to levels achieved upon PTEN deletion in combination with CNTF application/IS. 6,23,41,44,45 Conceivably, it might be possible to further increase the number and length of regenerating axons by applying AAV-hIL-6 prior to injury or by using combinations with other previously reported genetic approaches, 23,35,41,[46][47][48][49][50] as demonstrated by the combination of hIL-6 expression with RGC-specific PTEN knockout.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the degeneration process of RGCs is dramatically delayed and RGCs regenerate lengthy axons into a peripheral nerve graft or into the inhibitory environment of the injured optic nerve (Fig. 1a, c;Fischer et al 2000Fischer et al , 2001Leon et al 2000;Yin et al 2003;Sengottuvel et al 2011). In addition, lens injury increases the axonal growth rate, significantly alters gene expression and activates specific signaling pathways in RGCs (Fischer et al 2004b;Muller et al 2007;Leibinger et al 2009).…”
Section: Activation Of Intrinsic Growth State Of Mature Rgcs By Cytokmentioning
confidence: 94%
“…In vivo the application of an appropriate concentration of Taxol allows some axonal regrowth beyond the injury site and markedly enhances ISinduced regeneration in the optic nerve to a stronger extent than RhoA inhibition (Fig. 1b, Fischer et al 2004b;Sengottuvel et al 2011;Sengottuvel 2011). In addition to the direct effect of Taxol on the axonal growth cone, local application of the drug delays the formation of the glial scar, reduces the influx of macrophages and importantly, prevents the expression of inhibitory proteoglycans at the injury site (Hellal et al 2011;Sengottuvel et al 2011).…”
Section: Overcoming Inhibitory Signalingmentioning
confidence: 95%